The invention in the criticism of the Andalusian Muwashah (Journal of the College of Education for Women, 2019)
The research has arrived to the following results:1. There were critical views that accompanied the beginnings of (Muwashah). Theseviews were derived from literary criticism that handled the ancient Arabic poetry, especiallyits kinds that were concerned with artificiality in addition to the views based on rivalryamong makers of (Muwashah) in front of the audience so as to judje who is the bestaccording to artistic response.2. There existed new critical views, their originality was shown through the new criticaltheories that appeared especially those concerned with receiving the text and reading theory.3. The Muwashah was one of the most important poetic arts that reproduced previoustext, not in the traditional from which used implication or guotation, but in the creative formand this was supported by Sufi Washaheen who set out in their Sufi texts from the specialtheory of listening adopted by the Sufi doctrine. And thus some of their pieces ofMuwashah responded to the theorizing that took place about the inter text nality theory thatespecially adopts creative texts, and was one of the sublime models that enriched our Arabicliterature.